A high processing rheological adaptability automobile flame-retardant PVC composite heat stabilizer and a preparation process thereof

CN122917464APending Publication Date: 2026-10-16CHANGZHOU UKKA TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611368581.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但这些技术方案往往存在以下不足:一是水滑石的层间阴离子通常为碳酸根或硝酸根,与PVC基体的相容性较差,容易发生团聚,影响分散效果和热稳定效能;二是配方设计中缺乏对流变性能的系统考量,没有专门的流变调节组分,无法根据加工工艺需求调控PVC熔体的流变行为;三是阻燃功能与热稳定功能相互独立,没有实现阻燃协效剂与热稳定剂的有机复合,阻燃剂的加入往往会劣化热稳定性和加工性能;四是制备工艺简单,多为物理混合,各组分之间缺乏界面结合,容易在储存和运输过程中发生分层,影响使用效果

Benefits of technology

[0026] First, it exhibits excellent thermal stability. This invention uses a magnesium-aluminum-zinc ternary layered double hydroxide (LDH) as the primary stabilizer. The layered structure of the LDH allows for the adsorption of hydrogen chloride produced by the thermal degradation of PVC through interlayer anion exchange. Zinc ions on the layers can replace unstable chlorine atoms in the PVC molecular chain, while magnesium and aluminum ions neutralize hydrogen chloride and inhibit zinc burning. The synergistic effect of the ternary metal ions significantly enhances the thermal stability compared to traditional binary LDH. The polyol ester in the auxiliary stabilizer forms chelates with zinc ions, inhibiting their catalytic degradation; β-diketones undergo addition reactions with the conjugated polyene structures produced by PVC degradation, inhibiting discoloration; and phosphites react with peroxides, inhibiting oxidative degradation. The multi-component synergy of the primary and auxiliary stabilizers significantly improves both the static and dynamic thermal stability times of the composite thermal stabilizer, resulting in excellent initial colorability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of high processing rheological adaptability automobile flame-retardant PVC composite heat stabilizer and preparation process thereof, belong to high polymer material processing aid technical field.The composite heat stabilizer includes main stabilizer, auxiliary stabilizer, rheological modifier and flame-retardant synergist, main stabilizer is layered double metal hydroxide, auxiliary stabilizer includes polyhydric alcohol ester, beta-diketone and phosphite, rheological modifier is oxidized polyethylene wax, and flame-retardant synergist is the composite of ammonium molybdate and zinc borate.Preparation process includes steps such as water-sliding stone surface modification, flame-retardant synergist pre-composite, twice temperature gradient blending and cooling discharge.The composite heat stabilizer of the application has excellent thermal stabilization efficiency, high processing rheological adaptability, significant flame-retardant synergistic effect, excellent environmental performance, and is suitable for the processing and molding of automobile PVC composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer processing aids, specifically to a composite heat stabilizer for automotive polyvinyl chloride composite materials and its preparation process. Background Technology

[0002] Polyvinyl chloride (PVC) is one of the world's most produced general-purpose plastics. It possesses excellent mechanical properties, chemical resistance, electrical insulation, and flame retardancy, and is widely used in construction, automotive, electronics, and packaging. In the automotive industry, PVC is commonly used to manufacture interior parts, wire and cable sheaths, sealing strips, flooring, and headliner materials. However, the PVC molecular chain contains unstable structures such as allyl chloride and tertiary chloride, which are prone to thermal degradation during processing and use. This releases hydrogen chloride gas, leading to discoloration, decreased mechanical properties, and in severe cases, carbonization that renders the material unusable. Therefore, heat stabilizers must be added during PVC processing to inhibit thermal degradation.

[0003] Traditional PVC heat stabilizers mainly include lead salt stabilizers, barium cadmium stabilizers, organotin stabilizers, and calcium-zinc stabilizers. Lead salt stabilizers offer excellent thermal stability and are inexpensive, but lead is a heavy metal and toxic, thus its use in applications involving close contact with the human body, such as automotive interiors, is strictly limited. The EU's End-of-Life Vehicle Directive and China's requirements for prohibited substances in automobiles both explicitly restrict the use of lead. Barium cadmium stabilizers also have heavy metal toxicity issues and have been gradually phased out of the market. Organotin stabilizers offer excellent thermal stability and transparency, but are more expensive, and some varieties have an irritating odor, which can affect air quality in the confined space of a car. Calcium-zinc stabilizers are currently the mainstream direction for environmentally friendly stabilizers, but their thermal stabilization performance is limited, their initial colorability is poor, and they are difficult to use alone to meet the high-performance requirements of automotive PVC materials.

[0004] Furthermore, automotive PVC materials have specific requirements for rheological properties during processing. Automotive interior parts are typically molded using processes such as extrusion, calendering, and injection molding. During processing, rheological parameters such as the plasticizing time of the PVC melt, the equilibrium torque, and the processing temperature window directly affect production efficiency and product quality. Existing heat stabilizers often only focus on thermal stability, neglecting the control of PVC processing rheological properties. While some stabilizers can improve thermal stability, they can lead to problems such as excessively fast or slow plasticization of the PVC melt, excessively high or low equilibrium torque, and narrowed processing temperature windows, causing difficulties in the processing technology. Especially in high-speed extrusion and precision calendering processes, fluctuations in rheological properties can lead to uneven product thickness, decreased surface quality, and reduced production efficiency.

[0005] Meanwhile, PVC materials for automotive applications also need to meet stringent flame-retardant requirements. The flame-retardant performance of automotive interior materials is a crucial indicator of vehicle safety, and regulations in various countries have set clear requirements for the combustion rate of these materials. While PVC itself contains chlorine and possesses some flame-retardant properties, the addition of heat stabilizers during processing can affect its flame-retardant performance. Some environmentally friendly stabilizers incorporate large amounts of organic components to improve thermal stability; these organic components can produce flammable gases during combustion, reducing the material's flame-retardant rating. Therefore, developing a composite heat stabilizer that simultaneously possesses excellent thermal stability, good processing rheological compatibility, and synergistic flame-retardant effects is of great significance for the development of PVC materials for automotive applications.

[0006] Currently, there are some reports on composite heat stabilizers in existing technologies. For example, some patent documents disclose heat stabilizers composed of hydrotalcite and calcium zinc soap, utilizing the layered structure of hydrotalcite to adsorb hydrogen chloride and produce a synergistic effect with calcium zinc soap. However, these technical solutions often have the following shortcomings: First, the interlayer anions of hydrotalcite are usually carbonate or nitrate, which have poor compatibility with the PVC matrix and are prone to agglomeration, affecting the dispersion effect and heat stability performance; second, the formulation design lacks a systematic consideration of rheological properties, and there are no dedicated rheology adjustment components, making it impossible to control the rheological behavior of PVC melt according to processing requirements; third, the flame retardant function and the heat stabilizing function are independent of each other, failing to achieve an organic composite of flame retardant synergists and heat stabilizers, and the addition of flame retardants often degrades thermal stability and processing performance; fourth, the preparation process is simple, mostly involving physical mixing, and there is a lack of interfacial bonding between the components, making it easy for stratification to occur during storage and transportation, affecting the performance.

[0007] Therefore, there is an urgent need to develop a new type of PVC composite heat stabilizer for automobiles. Through the synergistic design of multiple components, it can simultaneously achieve excellent thermal stability, good processing rheological compatibility and flame retardant synergy. Furthermore, by optimizing the preparation process, it can improve the dispersibility and interfacial bonding of each component to meet the high-performance requirements of the automotive industry for PVC materials. Summary of the Invention Summary of the Invention

[0008] The purpose of this invention is to overcome the aforementioned shortcomings in the prior art and provide a highly adaptable automotive flame-retardant PVC composite heat stabilizer and its preparation process. This composite heat stabilizer, through a multi-component synergistic design of a primary stabilizer, auxiliary stabilizer, rheology modifier, and flame-retardant synergist, effectively regulates the processing rheological behavior of PVC melt while ensuring excellent thermal stability, broadening the processing temperature window, and also exhibiting flame-retardant synergistic effects. It is suitable for the processing and molding of automotive PVC composite materials.

[0009] To achieve the above objectives, the present invention adopts the following technical solution:

[0010] A highly adaptable automotive flame-retardant PVC composite heat stabilizer comprises, by weight, the following components: 40 to 60 parts of a primary stabilizer, 15 to 30 parts of a secondary stabilizer, 8 to 15 parts of a rheology modifier, and 10 to 20 parts of a flame-retardant synergist. The primary stabilizer is a layered bimetallic hydroxide; the secondary stabilizers include polyol esters, β-diketones, and phosphites; the rheology modifier is oxidized polyethylene wax; and the flame-retardant synergist is a complex of ammonium molybdate and zinc borate.

[0011] Furthermore, the layered bimetallic hydroxide is a magnesium-aluminum-zinc ternary hydrotalcite, wherein the molar ratio of magnesium, aluminum and zinc is 2:1:0.3 to 0.8, the interlayer anion is a composite anion of stearate and carbonate, and the average particle size is 500 nanometers to 2 micrometers.

[0012] Furthermore, the polyol ester is pentaerythritol stearate, the β-diketone is stearoylbenzoylmethane, and the phosphite ester is trinonylphenyl phosphite. By weight, the polyol ester is 8 to 15 parts, the β-diketone is 4 to 10 parts, and the phosphite ester is 3 to 5 parts.

[0013] Furthermore, the number-average molecular weight of the oxidized polyethylene wax is 1500 to 4000, the acid value is 10 to 25 mg potassium hydroxide per gram, and the dropping point is 100 to 120 degrees Celsius.

[0014] Furthermore, the mass ratio of ammonium molybdate to zinc borate in the flame retardant synergist is 1:2 to 1:4, and the average particle size of the flame retardant synergist is 1 to 3 micrometers.

[0015] Furthermore, the composite heat stabilizer also includes 1 to 3 parts by weight of a surface modifier, which is a silane coupling agent or a titanate coupling agent, and the surface of the layered bimetallic hydroxide is treated with the surface modifier.

[0016] The present invention also provides a preparation process for the above-mentioned composite heat stabilizer, comprising the following steps:

[0017] The first step involves adding the layered bimetallic hydroxide to a high-speed mixer and preheating it to 80 to 100 degrees Celsius. Then, a surface modifier diluted with ethanol is sprayed in and the mixture is stirred at 1000 to 1500 rpm for 15 to 30 minutes to obtain the modified layered bimetallic hydroxide.

[0018] The second step involves adding ammonium molybdate and zinc borate to a ball mill in a specific ratio, along with a dispersant, and then ball milling at 300 to 500 revolutions per minute for 2 to 4 hours to obtain a pre-composite flame retardant synergist.

[0019] The third step involves adding the modified layered bimetallic hydroxide and auxiliary stabilizer into a high-speed mixer and mixing them at 100 to 120 degrees Celsius and a speed of 800 to 1200 rpm for 10 to 20 minutes to obtain a primary blend.

[0020] The fourth step involves adding a rheology modifier and a pre-composite flame retardant synergist to the primary blend, and continuing to mix at 110 to 130 degrees Celsius and a rotation speed of 800 to 1200 rpm for 15 to 25 minutes to obtain a secondary blend.

[0021] The fifth step is to cool the secondary blend to below 60 degrees Celsius, discharge it, and then sieve it to obtain the composite heat stabilizer.

[0022] Furthermore, in the first step, the mass concentration of the surface modifier in the ethanol dilution solution is 20% to 30%, and the spray addition rate is 5 to 10 ml per minute. The material temperature in the high-speed mixer is controlled by the jacketed circulating water, and the temperature fluctuation does not exceed ±2 degrees Celsius.

[0023] Furthermore, in the second step, the dispersant is stearic acid, added at a rate of 0.5% to 1% of the total mass of ammonium molybdate and zinc borate. The ball mill uses zirconia balls as the grinding media, with a ball-to-material mass ratio of 3:1 to 5:1.

[0024] Furthermore, during the mixing processes in steps three and four, the lid of the high-speed mixer is closed, and the mixing chamber is filled with nitrogen for protection, with a nitrogen flow rate of 2 to 5 liters per minute. In step five, sieving is performed using a standard sieve of 80 to 120 mesh.

[0025] The metal-modified mineral-based composite sediment endogenous phosphorus stabilizing and remediating agent and its application method of the present invention have the following advantages compared with the prior art:

[0026] First, it exhibits excellent thermal stability. This invention uses a magnesium-aluminum-zinc ternary layered double hydroxide (LDH) as the primary stabilizer. The layered structure of the LDH allows for the adsorption of hydrogen chloride produced by the thermal degradation of PVC through interlayer anion exchange. Zinc ions on the layers can replace unstable chlorine atoms in the PVC molecular chain, while magnesium and aluminum ions neutralize hydrogen chloride and inhibit zinc burning. The synergistic effect of the ternary metal ions significantly enhances the thermal stability compared to traditional binary LDH. The polyol ester in the auxiliary stabilizer forms chelates with zinc ions, inhibiting their catalytic degradation; β-diketones undergo addition reactions with the conjugated polyene structures produced by PVC degradation, inhibiting discoloration; and phosphites react with peroxides, inhibiting oxidative degradation. The multi-component synergy of the primary and auxiliary stabilizers significantly improves both the static and dynamic thermal stability times of the composite thermal stabilizer, resulting in excellent initial colorability.

[0027] Secondly, it exhibits high adaptability to processing rheology. This invention specifically designs rheology modifier components, using oxidized polyethylene wax with a specific molecular weight and acid value to regulate the rheological behavior of PVC melt. The carboxyl and hydroxyl groups on the oxidized polyethylene wax molecular chain can form hydrogen bonds with the PVC molecular chain, promoting the breakage and plasticization of PVC resin particles in the early stages of processing and shortening the plasticization time. In the later stages of processing, the oxidized polyethylene wax migrates to the interface between the melt and the metal equipment, acting as an external lubricant, reducing the equilibrium torque, and decreasing the frictional heat between the melt and the equipment. By controlling the molecular weight, acid value, and dosage of the oxidized polyethylene wax, the plasticization time and equilibrium torque of the PVC melt can be precisely adjusted to adapt to different processing requirements. Simultaneously, the surface modification treatment of the main stabilizer and auxiliary stabilizer improves the dispersibility of each component in the PVC matrix, reduces rheological fluctuations caused by agglomeration, and makes the processing more stable.

[0028] Third, the flame-retardant synergistic effect is significant. This invention uses ammonium molybdate and zinc borate pre-composite as a flame-retardant synergist, achieving an organic combination of flame-retardant and thermal stability functions. When heated, ammonium molybdate decomposes, releasing ammonia and water vapor, diluting the concentration of combustible gases. Simultaneously, the generated molybdenum oxide promotes charring in PVC, forming a dense char layer that blocks heat and oxygen transfer. Zinc borate, at high temperatures, forms a glassy borate coating layer, isolating oxygen and heat while suppressing smoke generation. The synergistic effect of ammonium molybdate and zinc borate makes the flame-retardant performance significantly superior to that of a single flame retardant. Furthermore, the pre-composite treatment of the flame-retardant synergist improves its dispersibility in the composite thermal stabilizer, avoiding the agglomeration problem caused by direct addition, resulting in a more uniform and stable flame-retardant effect.

[0029] Fourth, the preparation process is reasonable, and the product quality is stable. This invention employs a stepwise blending process. First, the surface of the hydrotalcite is modified to improve its compatibility with organic components. Then, the flame retardant synergist is pre-composite-treated to achieve uniform mixing of ammonium molybdate and zinc borate. Finally, two temperature gradient mixing processes ensure that the components are fully dispersed and form interfacial bonds. Nitrogen protection effectively prevents the oxidative degradation of organic components during high-temperature mixing, ensuring the stability of product quality. The preparation process does not involve the large-scale use of organic solvents, is simple to operate, and is easy to industrialize.

[0030] Fifth, it has excellent environmental performance. The composite heat stabilizer of this invention does not contain heavy metals such as lead, cadmium, and barium, nor does it contain components with irritating odors such as organotin. It meets the requirements for prohibited substances in automobiles and in-vehicle air quality standards, and is suitable for applications with high environmental protection requirements, such as automotive interior parts and wire and cable sheaths. Detailed Implementation

[0031] To make the technical solution, implementation details, and beneficial effects of the present invention clearer, the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the scope of protection of the present invention. Other embodiments obtained by those skilled in the art without creative effort based on the core concept of the present invention are all within the scope of protection of the present invention.

[0032] The composite heat stabilizer of this invention comprises a primary stabilizer, an auxiliary stabilizer, a rheology modifier, a flame retardant synergist, and a surface modifier. The mechanisms of action and selection criteria for each component are as follows:

[0033] The main stabilizer is magnesium-aluminum-zinc ternary hydrotalcite, which belongs to layered bimetallic hydroxides. The general chemical formula of layered bimetallic hydroxides is: divalent metal ion 1 - x trivalent metal ion x hydroxide ion 2 anion n - x divided by n multiplied by water of crystallization m, where the divalent metal ions include magnesium and zinc ions, the trivalent metal ion is aluminum ion, and the interlayer anions are stearate and carbonate ions. This invention selects magnesium ions as the main divalent metal ion, zinc ions as the auxiliary divalent metal ion, and aluminum ions as the trivalent metal ion. Magnesium hydroxide has moderate alkalinity and can effectively neutralize hydrogen chloride; zinc ions can undergo a substitution reaction with unstable chlorine atoms in the PVC molecular chain, converting unstable structures such as allyl chloride into stable carbon-zinc bonds, thereby inhibiting the initiation of thermal degradation; aluminum ions constitute the framework structure of the layers, providing stability to the layered structure. The synergistic effect of the three metal ions gives hydrotalcite both excellent initial coloring inhibition ability and long-term thermal stability.

[0034] The molar ratio of magnesium, aluminum, and zinc should be controlled within the range of 2:1:0.3 to 0.8. If the zinc content is too low, the initial coloring inhibition ability is insufficient; if the zinc content is too high, zinc burning is likely to occur, meaning that zinc chloride generated during the thermal degradation of zinc ions will further catalyze the degradation of PVC, causing the material to turn black rapidly. Extensive experimental verification has shown that when the molar ratio of zinc to aluminum is within the range of 0.3 to 0.8, the optimal balance between initial coloring and long-term thermal stability can be achieved.

[0035] The interlayer anion is a composite anion of stearate and carbonate. Traditional hydrotalcites primarily use carbonate or nitrate as interlayer anions, which have poor compatibility with the PVC matrix, leading to easy aggregation of hydrotalcite within PVC. This invention replaces some carbonate with stearate through ion exchange. The long carbon chain structure of stearate significantly improves the compatibility and dispersibility of hydrotalcite with the PVC matrix. Simultaneously, stearate can form metal soaps with metal ions on the layers upon heating, further enhancing thermal stability. The molar ratio of stearate to carbonate is controlled within the range of 1:1 to 1:3. Excessive stearate content reduces the interlayer anion exchange capacity of the hydrotalcite, affecting its hydrogen chloride adsorption capacity; conversely, insufficient stearate content results in minimal improvement in compatibility.

[0036] The average particle size of the hydrotalcite is controlled within the range of 500 nanometers to 2 micrometers. If the particle size is too large, the specific surface area is small, limiting the contact area with PVC and resulting in insufficient thermal stability. If the particle size is too small, the surface energy is high, making agglomeration more likely and negatively impacting dispersion. A particle size range of 500 nanometers to 2 micrometers achieves a good balance between specific surface area and dispersibility.

[0037] The auxiliary stabilizers include three components: polyol esters, β-diketones, and phosphites. They work synergistically with the main stabilizers to further improve thermal stability.

[0038] The polyol ester selected is pentaerythritol stearate. Pentaerythritol stearate contains multiple hydroxyl groups, which can form stable chelates with zinc ions, inhibiting the catalytic degradation of zinc ions and effectively preventing zinc burning. Simultaneously, pentaerythritol stearate has a certain lubricating effect, improving the processing rheological properties of PVC. The addition amount of pentaerythritol stearate is 8 to 15 parts by weight. Too low an addition amount results in insufficient chelation, failing to effectively inhibit zinc burning; too high an addition amount excessively reduces the viscosity of the PVC melt, affecting the mechanical properties of the product.

[0039] Stearoylbenzoylmethane is selected as the β-diketone. Stearoylbenzoylmethane is a commonly used auxiliary stabilizer for PVC. Its β-diketone structure can undergo a Diels-Alder addition reaction with the conjugated polyene structure produced by the thermal degradation of PVC, disrupting the conjugated system and thus inhibiting discoloration. Furthermore, stearoylbenzoylmethane can form a complex with zinc ions, improving the stability of zinc ions. The addition amount of stearoylbenzoylmethane is 4 to 10 parts by weight. Too low an addition amount results in insignificant discoloration inhibition; too high an addition amount leads to blooming on the product surface, affecting its appearance.

[0040] Trinonylphenyl phosphite is selected as the phosphite. Phosphite is a co-antioxidant that reacts with peroxides, reducing them to stable alcohol compounds, thereby inhibiting the oxidative degradation of PVC. Simultaneously, phosphite can form complexes with metal ions, passivating their catalytic activity. Trinonylphenyl phosphite has low volatility and good hydrolysis resistance, making it suitable for high-temperature processing. The addition amount of trinonylphenyl phosphite is 3 to 5 parts by weight. Too low a dosage results in insufficient antioxidant effect; too high a dosage will produce odors during processing, affecting the air quality inside the vehicle.

[0041] Oxidized polyethylene wax was selected as the rheology modifier. Oxidized polyethylene wax is a product obtained by oxidizing and modifying polyethylene wax, introducing polar groups such as carboxyl and hydroxyl groups into its molecular chain. Oxidized polyethylene wax provides both internal and external lubrication in PVC processing: in the initial stage of processing, the polar groups of oxidized polyethylene wax interact with the PVC molecular chain, promoting the breakage and gelation of PVC resin particles and shortening the plasticizing time; in the later stage of processing, oxidized polyethylene wax migrates to the interface between the melt and the metal equipment, forming a lubricating film, reducing friction between the melt and the equipment, reducing frictional heat generation, and lowering the equilibrium torque.

[0042] The number-average molecular weight of oxidized polyethylene wax is controlled within the range of 1500 to 4000. If the molecular weight is too low, the melting point of the oxidized polyethylene wax is low, making it prone to premature precipitation during processing and resulting in a short duration of lubrication. If the molecular weight is too high, the viscosity of the oxidized polyethylene wax is high, reducing its compatibility with PVC and making it prone to forming deposits on the product surface. A number-average molecular weight range of 1500 to 4000 ensures that the oxidized polyethylene wax provides stable lubrication throughout the entire PVC processing process.

[0043] The acid value of oxidized polyethylene wax is controlled within the range of 10 to 25 mg / g of potassium hydroxide. The acid value reflects the content of polar groups on the molecular chain of oxidized polyethylene wax. If the acid value is too low, the content of polar groups is insufficient, resulting in poor compatibility with PVC and insignificant internal lubrication. If the acid value is too high, the content of polar groups is excessive, increasing the hydrophilicity of the oxidized polyethylene wax and making it prone to absorbing moisture, leading to the formation of bubbles in PVC products during processing. An acid value range of 10 to 25 mg / g of potassium hydroxide achieves a good balance between lubrication performance and water resistance.

[0044] The dropping point of oxidized polyethylene wax is controlled within the range of 100 to 120 degrees Celsius. The dropping point refers to the temperature at which a wax substance begins to drip under specified conditions, reflecting the wax's melting point range. If the dropping point is too low, the oxidized polyethylene wax will melt and precipitate in the early stages of processing, failing to provide external lubrication in the later stages. If the dropping point is too high, the oxidized polyethylene wax will not melt completely at the processing temperature, resulting in uneven lubrication. A dropping point range of 100 to 120 degrees Celsius matches the commonly used processing temperature range for PVC, ensuring that the oxidized polyethylene wax melts gradually during processing and continues to provide lubrication.

[0045] The flame retardant synergist is a complex of ammonium molybdate and zinc borate. Both ammonium molybdate and zinc borate are commonly used inorganic flame retardants. They have different flame retardant mechanisms in PVC, and their combined use can produce a synergistic effect.

[0046] Ammonium molybdate decomposes upon heating, releasing ammonia and water vapor. The ammonia and water vapor dilute the concentration of combustible gases produced by the thermal degradation of PVC, reducing the rate of combustion. Simultaneously, the molybdenum oxide generated from the decomposition of ammonium molybdate acts as a Lewis acid catalyst, promoting the cross-linking and charring of PVC molecular chains, forming a dense char layer on the material surface. This char layer blocks heat and oxygen from transferring into the material and inhibits the escape of combustible gases, thus exerting a flame-retardant effect.

[0047] Zinc borate loses its water of crystallization at high temperatures, absorbing a large amount of heat and lowering the surface temperature of the material. Simultaneously, zinc borate melts at high temperatures to form a glassy borate coating, covering the material surface and isolating it from oxygen and heat. Furthermore, zinc borate reacts with hydrogen chloride produced during PVC degradation to generate zinc chloride and boric acid. Zinc chloride further promotes char formation, while boric acid forms a glassy protective layer. Zinc borate also has a smoke-suppressing effect, reducing the amount of smoke generated during combustion.

[0048] The mass ratio of ammonium molybdate to zinc borate should be controlled within the range of 1:2 to 1:4. If the ammonium molybdate content is too high, excessive ammonia gas will be generated during decomposition, leading to bubbles in PVC products during processing; if the ammonium molybdate content is too low, the char-forming catalytic effect will be insufficient, resulting in a decrease in flame retardant performance. Experimental verification has shown that a mass ratio of 1:2 to 1:4 achieves the optimal balance between flame retardant performance and processing properties.

[0049] The average particle size of the flame retardant synergist is controlled within the range of 1 to 3 micrometers. If the particle size is too large, the flame retardant synergist has poor dispersibility in PVC, easily forming agglomerates and affecting the uniformity of the flame retardant effect; if the particle size is too small, the particle surface energy is high, making secondary agglomeration prone to occur during pre-composite and blending processes. A particle size range of 1 to 3 micrometers ensures uniform dispersion of the flame retardant synergist in the composite heat stabilizer and PVC matrix.

[0050] Surface modifiers are selected from silane coupling agents or titanate coupling agents. Silane coupling agents can be γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane, while titanate coupling agents can be isopropyltrioleyloxytitanate. The role of the surface modifier is to form an organic coating layer on the surface of the hydrotalcite particles, improving the compatibility of hydrotalcite with the PVC matrix and organic auxiliary stabilizers. The alkoxy groups in the silane coupling agent molecule can undergo a condensation reaction with the hydroxyl groups on the hydrotalcite surface to form covalent bonds; the organic functional groups in the molecule can physically entangle or chemically interact with the PVC molecular chains, thereby enhancing interfacial bonding. Titanate coupling agents, through the reaction of monoalkoxy groups with the hydroxyl groups on the hydrotalcite surface, with the long-chain alkyl groups facing outwards, provide good compatibility.

[0051] The amount of surface modifier added is 1 to 3 parts by weight. If the amount added is too low, the coating on the surface of the hydrotalcite will be incomplete, and the compatibility improvement effect will not be obvious; if the amount added is too high, the excessive coupling agent will form a multilayer adsorption on the surface of the hydrotalcite particles, which will weaken the interfacial bonding force and generate small molecule volatiles during processing, affecting product quality.

[0052] The preparation process of the composite heat stabilizer of the present invention is described in detail below:

[0053] The first step is the surface modification treatment of the hydrotalcite. Magnesium-aluminum-zinc ternary hydrotalcite is added to a high-speed mixer, and the stirring and heating systems are turned on to preheat the material to 80-100 degrees Celsius. Preheating removes adsorbed moisture from the surface of the hydrotalcite particles and enhances the reactivity of the surface hydroxyl groups. The surface modifier is diluted with ethanol to a mass concentration of 20%-30%, and then uniformly sprayed into the high-speed mixer at a rate of 5-10 ml / min using a spray device. Spraying allows the coupling agent solution to form fine droplets that evenly cover the surface of the hydrotalcite particles, preventing agglomeration caused by excessively high local concentrations. After spraying, stirring continues at 1000-1500 rpm for 15-30 minutes to ensure the coupling agent fully reacts with the hydroxyl groups on the hydrotalcite surface. The material temperature in the high-speed mixer is controlled by the jacketed circulating water, with temperature fluctuations not exceeding ±2 degrees Celsius to ensure the stability of the reaction conditions. After the reaction is complete, a modified layered bimetallic hydroxide is obtained.

[0054] The second step is the pre-composite treatment of the flame retardant synergist. Ammonium molybdate and zinc borate are added to a ball mill at a mass ratio of 1:2 to 1:4, along with stearic acid as a dispersant, at a concentration of 0.5% to 1% of the total mass of ammonium molybdate and zinc borate. Stearic acid coats the surface of inorganic particles during grinding, reducing their surface energy and preventing secondary agglomeration. Zirconia balls are used as the grinding medium, with a ball-to-particle mass ratio of 3:1 to 5:1, and the milling process is carried out at 300 to 500 rpm for 2 to 4 hours. During ball milling, the ammonium molybdate and zinc borate particles are refined and thoroughly mixed, and the stearic acid coats the particle surface, resulting in a pre-composite flame retardant synergist. This pre-composite treatment ensures uniform mixing of ammonium molybdate and zinc borate at the microscale, which helps maintain the uniformity of their proportions during subsequent blending and avoids component segregation caused by direct mixing.

[0055] The third step is primary blending. The modified layered bimetallic hydroxide obtained in the first step, along with auxiliary stabilizers including pentaerythritol stearate, stearoyl benzoylmethane, and trinonylphenyl phosphite, are added to a high-speed mixer in the specified proportions. The stirring and heating systems are turned on, and the mixture is stirred for 10 to 20 minutes at 100 to 120 degrees Celsius and a speed of 800 to 1200 rpm. The temperature of the primary blending is controlled near or slightly above the melting point of the auxiliary stabilizers, allowing them to partially melt during the mixing process and coat the surface of the modified hydrotalcite particles, forming organic-inorganic composite particles. The shear force generated by high-speed stirring breaks up the agglomerates, ensuring thorough dispersion of the components. During the mixing process, the lid of the high-speed mixer is closed, and the mixing chamber is filled with nitrogen gas at a flow rate of 2 to 5 liters per minute to prevent oxidative degradation of the auxiliary stabilizers at high temperatures. After mixing, the primary blend is obtained.

[0056] The fourth step is secondary blending. The rheology modifier oxidized polyethylene wax and the pre-composite flame retardant synergist obtained in the second step are added to the primary blend obtained in the third step. The mixture is then stirred for 15 to 25 minutes at 110 to 130 degrees Celsius and a rotation speed of 800 to 1200 rpm. The temperature of the secondary blending is slightly higher than that of the primary blending, ensuring that the oxidized polyethylene wax is fully melted and uniformly dispersed in the system. The melting of the oxidized polyethylene wax forms a lubricating layer on the surface of each component particle, reducing friction between particles and promoting dispersion. The addition of the pre-composite flame retardant synergist at this step prevents the decomposition of ammonium molybdate caused by prolonged exposure to high temperatures. Nitrogen protection is maintained throughout the mixing process. After mixing, the secondary blend is obtained.

[0057] The fifth step is cooling and discharging. The secondary blend obtained in the fourth step is cooled to below 60 degrees Celsius, with low-speed stirring maintained during the cooling process to prevent particle agglomeration. After cooling to below 60 degrees Celsius, the material is discharged and passed through an 80-120 mesh standard sieve to remove agglomerates and impurities, yielding the composite heat stabilizer product of this invention. The finished product is a white to pale yellow powder solid with a bulk density of 0.4 to 0.6 g / cm³ and a moisture content not exceeding 0.5%.

[0058] The recommended addition amount of the composite heat stabilizer of this invention in automotive PVC composite materials is 3 to 8 parts by weight per 100 parts by weight of PVC resin. If the addition amount is too low, the heat stabilization performance will be insufficient and unable to meet processing requirements; if the addition amount is too high, it will affect the mechanical properties and transparency of PVC products and increase costs.

[0059] The technical effects of the present invention will be described below through specific embodiments.

[0060] Example 1:

[0061] A high-processing-rheology-adaptive automotive flame-retardant PVC composite heat stabilizer comprises the following components by weight: 50 parts magnesium-aluminum-zinc ternary hydrotalcite, 10 parts pentaerythritol stearate, 7 parts stearoylbenzoylmethane, 4 parts trinonylphenyl phosphite, 12 parts oxidized polyethylene wax, 15 parts ammonium molybdate-zinc borate complex, and 2 parts silane coupling agent.

[0062] The magnesium-aluminum-zinc ternary hydrotalcite contains magnesium, aluminum, and zinc in a molar ratio of 2:1:0.5. The interlayer anion is a composite anion of stearate and carbonate, with a stearate to carbonate molar ratio of 1:2. The average particle size is 1 micrometer. The oxidized polyethylene wax has a number-average molecular weight of 2500, an acid value of 18 mg / g potassium hydroxide, and a dropping point of 110°C. The flame retardant synergist contains ammonium molybdate to zinc borate in a mass ratio of 1:3, with an average particle size of 2 micrometers. The silane coupling agent is γ-aminopropyltriethoxysilane.

[0063] The preparation process is as follows:

[0064] The first step involves adding the magnesium-aluminum-zinc ternary hydrotalcite to a high-speed mixer and preheating it to 90 degrees Celsius. The silane coupling agent is diluted with ethanol to a 25% (w / w) solution and sprayed in at a rate of 8 ml / min. The mixture is then stirred at 1200 rpm for 20 minutes to obtain the modified hydrotalcite.

[0065] The second step involves adding ammonium molybdate and zinc borate to a ball mill at a mass ratio of 1:3, adding stearic acid at a mass ratio of 0.8% of the total mass, using zirconia balls as the grinding medium at a mass ratio of 4:1, and ball milling at 400 rpm for 3 hours to obtain the pre-composite flame retardant synergist.

[0066] The third step involves adding modified hydrotalcite, pentaerythritol stearate, stearoyl benzoylmethane, and trinonylphenyl phosphite into a high-speed mixer and mixing for 15 minutes at 1000 rpm at 110 degrees Celsius with a nitrogen flow rate of 3 liters per minute to obtain a primary blend.

[0067] The fourth step involves adding oxidized polyethylene wax and a pre-composite flame retardant synergist to the primary blend, mixing it at 120 degrees Celsius and a rotation speed of 1000 rpm for 20 minutes with a nitrogen flow rate of 3 liters per minute to obtain the secondary blend.

[0068] The fifth step is to cool the secondary blend to 50 degrees Celsius, discharge it, and pass it through a 100-mesh standard sieve to obtain the finished composite heat stabilizer.

[0069] Example 2:

[0070] The difference from Example 1 is that the molar ratio of magnesium, aluminum, and zinc in the magnesium-aluminum-zinc ternary hydrotalcite is 2:1:0.3; the number-average molecular weight of the oxidized polyethylene wax is 1500; the acid value is 10 mg / g of potassium hydroxide; the dropping point is 100°C; and the mass ratio of ammonium molybdate to zinc borate in the flame retardant synergist is 1:2. The weight parts of each component are: 40 parts magnesium-aluminum-zinc ternary hydrotalcite, 8 parts pentaerythritol stearate, 4 parts stearoylbenzoylmethane, 3 parts trinonylphenyl phosphite, 8 parts oxidized polyethylene wax, 10 parts ammonium molybdate-zinc borate complex, and 1 part silane coupling agent.

[0071] Example 3:

[0072] The difference from Example 1 is that the molar ratio of magnesium, aluminum, and zinc in the magnesium-aluminum-zinc ternary hydrotalcite is 2:1:0.8; the number-average molecular weight of the oxidized polyethylene wax is 4000; the acid value is 25 mg / g of potassium hydroxide; the dropping point is 120°C; and the mass ratio of ammonium molybdate to zinc borate in the flame retardant synergist is 1:4. The weight parts of each component are: 60 parts magnesium-aluminum-zinc ternary hydrotalcite, 15 parts pentaerythritol stearate, 10 parts stearoylbenzoylmethane, 5 parts trinonylphenyl phosphite, 15 parts oxidized polyethylene wax, 20 parts ammonium molybdate-zinc borate complex, and 3 parts silane coupling agent.

[0073] Comparative Example 1:

[0074] Ordinary magnesium-aluminum binary hydrotalcite was used as the main stabilizer, without the addition of zinc. The remaining components and preparation process were the same as in Example 1.

[0075] Comparative Example 2:

[0076] Without adding oxidized polyethylene wax rheology modifier, the remaining components and preparation process are the same as in Example 1.

[0077] Comparative Example 3:

[0078] No flame retardant synergist was added; the remaining components and preparation process were the same as in Example 1.

[0079] Comparative Example 4:

[0080] The traditional lead salt stabilizer, namely a complex of tribasic lead sulfate and dibasic lead phosphite, is used, with an addition amount of 5 parts by weight.

[0081] Performance testing:

[0082] The heat stabilizers from the above examples and comparative examples were added to the PVC formulation. The PVC formulation consisted of: 100 parts PVC resin, 40 parts dioctyl phthalate, 20 parts calcium carbonate, 0.5 parts stearic acid, and 5 parts heat stabilizer. The mixture was kneaded for 5 minutes at 170 degrees Celsius using a two-roll mill, and then stretched into sheets for performance testing.

[0083] The static thermal stability test was conducted according to GB / T2917.1 standard. The sample was placed in a glycerol bath at 180 degrees Celsius, and the time when the sample began to turn black was recorded.

[0084] Dynamic thermal stability testing was performed using a torque rheometer. The time from sample addition to the appearance of decomposition peak was recorded at 180 degrees Celsius and 50 revolutions per minute.

[0085] Rheological performance testing was performed using a torque rheometer, and the plasticizing time and equilibrium torque were recorded at 170 degrees Celsius and 50 revolutions per minute.

[0086] Flame retardant performance testing was conducted according to GB / T8410 standard, testing the horizontal burning rate of the sample.

[0087] The test results are as follows: Example 1: Static thermal stability time was 85 minutes, dynamic thermal stability time was 25 minutes, plasticizing time was 45 seconds, balance torque was 18 Nm, and burning rate was 35 mm / min. Example 2: Static thermal stability time was 72 minutes, dynamic thermal stability time was 21 minutes, plasticizing time was 52 seconds, balance torque was 20 Nm, and burning rate was 42 mm / min. Example 3: Static thermal stability time was 80 minutes, dynamic thermal stability time was 23 minutes, plasticizing time was 40 seconds, balance torque was 16 Nm, and burning rate was 38 mm / min. Comparative Example 1: Static thermal stability time was 55 minutes, dynamic thermal stability time was 16 minutes, plasticizing time was 48 seconds, balance torque was 19 Nm, and burning rate was 40 mm / min. Comparative Example 2: Static thermal stability time was 82 minutes, dynamic thermal stability time was 24 minutes, plasticizing time was 68 seconds, balance torque was 25 Nm, and burning rate was 36 mm / min. Comparative Example 3 had a static thermal stabilization time of 84 minutes, a dynamic thermal stabilization time of 24 minutes, a plasticizing time of 46 seconds, a balance torque of 18 Nm, and a combustion rate of 68 mm / min. Comparative Example 4 had a static thermal stabilization time of 90 minutes, a dynamic thermal stabilization time of 28 minutes, a plasticizing time of 50 seconds, a balance torque of 19 Nm, and a combustion rate of 45 mm / min.

[0088] The test results show that the composite heat stabilizer of this invention exhibits excellent performance in terms of thermal stability, rheological properties, and flame retardant properties. Compared with Comparative Example 1, the static thermal stability time of Example 1 increased by 54.5%, and the dynamic thermal stability time increased by 56.3%, indicating that the introduction of zinc significantly improved the thermal stability efficiency. Compared with Comparative Example 2, the plasticizing time of Example 1 was shortened by 33.8%, and the equilibrium torque was reduced by 28%, indicating that the oxidized polyethylene wax rheology modifier can effectively improve the processing rheological properties of PVC. Compared with Comparative Example 3, the burning rate of Example 1 was reduced by 48.5%, indicating that the flame retardant synergist has a significant flame retardant synergistic effect. Compared with the traditional lead salt stabilizer of Comparative Example 4, although the thermal stability of Example 1 is slightly lower, it still meets the processing requirements, and its rheological and flame retardant properties are superior. Furthermore, it does not contain heavy metals and has excellent environmental performance. The above test data are based on the formulation and test conditions described in this embodiment and are not extrapolated to other formulation ratios and test conditions.

[0089] This invention also provides two core algorithms for use with the aforementioned composite heat stabilizers, which quantitatively characterize the action of the composite heat stabilizers from two dimensions: rheological properties and thermal stability effectiveness, providing theoretical guidance for formulation optimization. Both algorithms are based on classic theoretical models in the field of polymer materials, with clearly defined physical meanings for the parameters. Those skilled in the art can determine the model parameters and apply the algorithms using conventional experimental methods.

[0090] The first algorithm is a power-law model-based method for calculating the apparent viscosity of PVC melt. PVC melt is a typical pseudoplastic non-Newtonian fluid, and its rheological behavior conforms to the power-law equation widely used in polymer rheology, also known as the Ostwald-DeWall equation. This equation is a classical constitutive model describing the relationship between the shear viscosity and shear rate of polymer melts, and its theoretical basis is the orientation and deentanglement behavior of polymer molecular chains in a shear flow field. The expression of this algorithm is:

[0091] η equals K multiplied by γ raised to the power of n minus 1

[0092] Where η is the apparent viscosity of the PVC melt, measured in Pascals per second; K is the consistency coefficient, measured in Pascals per second to the power of n, reflecting the viscosity of the melt at low shear rates, and its value is determined by the molecular weight of the PVC resin, the plasticizer content, and the type and amount of the composite heat stabilizer; γ is the shear rate, measured in negative first power per second, calculated from the screw speed, roller linear velocity, or die flow channel geometry of the processing equipment; n is the non-Newtonian exponent, dimensionless, reflecting the degree of shear thinning of the melt. When n is less than 1, the melt exhibits shear thinning behavior. The closer n is to 1, the closer the melt is to a Newtonian fluid. The value of n is affected by the dispersion state of each component in the composite heat stabilizer in the PVC matrix.

[0093] The physical meaning of this algorithm is as follows: The oxidized polyethylene wax in the composite heat stabilizer reduces the internal friction and entanglement density between PVC molecular chains through internal lubrication, thus decreasing the consistency coefficient K and apparent viscosity, thereby shortening the plasticizing time and reducing the equilibrium torque. The surface-modified magnesium-aluminum-zinc ternary hydrotalcite is uniformly dispersed in the PVC matrix, reducing local viscosity fluctuations caused by inorganic particle agglomerates, and keeping the non-Newtonian index n stable within the processing shear rate range, thereby ensuring the consistency of rheological behavior during processing. The apparent viscosity of the PVC melt is measured at different shear rates using a rotational rheometer or capillary rheometer. The K and n values ​​can be obtained by performing a double logarithmic fitting on the experimental data; the fitting method is a conventional technique in this field. This power-law model is a classical constitutive equation in polymer rheology, with sufficient theoretical basis and clear physical meaning of the model parameters. Those skilled in the art can understand its origin and apply it to formulation evaluation.

[0094] The second algorithm is a synergistic evaluation method for the thermal stability performance of composite heat stabilizers. This method calculates the total thermal stability performance of the composite system using a superposition model, based on the independent thermal stability contribution of each component and the synergistic effect between components. Its theoretical basis is the isoline method principle in the evaluation of synergistic effects of polymeric additives. The expression for this algorithm is:

[0095] T equals the sum of T0 plus ci multiplied by ki plus ci multiplied by cj multiplied by kij, where i is less than j.

[0096] Wherein, T is the static thermal stability time of PVC after adding the composite heat stabilizer, in minutes; T0 is the static thermal stability time of blank PVC without any stabilizer added, in minutes; ci is the mass fraction of the i-th component in the PVC formulation, in percentage; ki is the single-component thermal stability contribution coefficient of the i-th component, in percentage per minute, representing the contribution of a unit mass fraction of this component to the thermal stability time when used alone, determined through single-component addition experiments; kij is the synergistic effect coefficient between the i-th and j-th components, in squared percentage per minute, a positive value indicates a synergistic effect between the two components, a negative value indicates an antagonistic effect between the two components, and a zero value indicates a simple additive relationship between the two components, determined through the isoline method experiment.

[0097] The physical meaning of this algorithm is that the thermal stabilization efficiency of composite heat stabilizers depends not only on the independent contribution of each individual component, but also on the synergistic effect between the components. For example, there is a synergistic effect between magnesium-aluminum-zinc ternary hydrotalcite and pentaerythritol stearate. After the hydrotalcite adsorbs hydrogen chloride through interlayer anion exchange, zinc ions on the layer are released into the PVC matrix. Multiple hydroxyl groups in the pentaerythritol stearate molecule form chelates with zinc ions, inhibiting the zinc burning phenomenon that catalyzes the degradation of PVC by zinc ions, thus making the synergistic effect coefficient kij a positive value. There is also a synergistic effect between stearoylbenzoylmethane and trinonylphenyl phosphite. The former inhibits discoloration by undergoing an addition reaction with the conjugated polyene structure, while the latter inhibits oxidative degradation by decomposing peroxides. The two inhibit the thermal degradation process through different reaction pathways, and the synergistic effect coefficient is also positive. The synergistic effect coefficient is determined using the equivalent line method. This involves keeping the total amount of the two components constant while gradually changing their mass ratio. The thermal stability time is measured for each ratio, and an equivalent curve is plotted to show the change in thermal stability time with the ratio. This curve is then compared to a straight line obtained by simply adding the two components. If the curve is above the straight line, it indicates synergistic effect; if it is below, it indicates antagonistic effect. The synergistic effect coefficient can be calculated based on the degree of deviation. This method is the standard method for evaluating the synergistic effect of polymeric additives. It has a sound theoretical basis, and those skilled in the art can understand its principle and apply it to experimental determination.

[0098] The two algorithms described above quantitatively evaluate the performance of composite heat stabilizers from two core dimensions: rheological properties and thermal stability effectiveness. The models are simple, the physical meanings are clear, and the theoretical basis is sufficient. Those skilled in the art can determine the model parameters through conventional experimental methods and apply the algorithms to optimize the formulation.

[0099] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the technical concept and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A high-processing-rheology-adaptive automotive flame-retardant PVC composite heat stabilizer, characterized in that, It includes a primary stabilizer, a secondary stabilizer, a rheology modifier, and a flame retardant synergist; the primary stabilizer is a layered double metal hydroxide, the secondary stabilizer includes polyol esters, β-diketones, and phosphites, the rheology modifier is oxidized polyethylene wax, and the flame retardant synergist is a complex of ammonium molybdate and zinc borate.

2. The composite heat stabilizer according to claim 1, characterized in that, By weight, the primary stabilizer comprises 40 to 60 parts, the auxiliary stabilizer comprises 15 to 30 parts, the rheology modifier comprises 8 to 15 parts, and the flame retardant synergist comprises 10 to 20 parts.

3. The composite heat stabilizer according to claim 1, characterized in that, The layered bimetallic hydroxide is a magnesium-aluminum-zinc ternary hydrotalcite, wherein the molar ratio of magnesium, aluminum and zinc is 2:1:0.3 to 0.8, the interlayer anion is a composite anion of stearate and carbonate, and the average particle size is 500 nanometers to 2 micrometers.

4. The composite heat stabilizer according to claim 1, characterized in that, The polyol ester is pentaerythritol stearate, the β-diketone is stearoylbenzoylmethane, and the phosphite is trinonylphenyl phosphite; by weight, the polyol ester is 8 to 15 parts, the β-diketone is 4 to 10 parts, and the phosphite is 3 to 5 parts.

5. The composite heat stabilizer according to claim 1, characterized in that, The oxidized polyethylene wax has a number-average molecular weight of 1,500 to 4,000, an acid value of 10 to 25 mg potassium hydroxide per gram, and a dropping point of 100 to 120 degrees Celsius.

6. The composite heat stabilizer according to claim 1, characterized in that, The mass ratio of ammonium molybdate to zinc borate in the flame retardant synergist is 1:2 to 1:4, and the average particle size of the flame retardant synergist is 1 to 3 micrometers.

7. The composite heat stabilizer according to any one of claims 1 to 6, characterized in that, It also includes 1 to 3 parts by weight of a surface modifier, wherein the surface modifier is a silane coupling agent or a titanate coupling agent, and the surface of the layered bimetallic hydroxide is treated with the surface modifier.

8. A preparation process for the composite heat stabilizer as described in any one of claims 1 to 7, characterized in that, Includes the following steps: The first step involves adding the layered bimetallic hydroxide to a high-speed mixer and preheating it to 80-100 degrees Celsius. A surface modifier diluted with ethanol is then sprayed in, and the mixture is stirred at 1000-1500 rpm for 15-30 minutes to obtain the modified layered bimetallic hydroxide. The second step involves adding ammonium molybdate and zinc borate in a specific ratio to a ball mill, along with a dispersant, and ball milling at 300-500 rpm for 2-4 hours to obtain the pre-composite flame retardant synergist. The third step involves combining the modified layered bimetallic hydroxide with an auxiliary stabilizer... The stabilizer is added to a high-speed mixer and mixed at 100 to 120 degrees Celsius at a speed of 800 to 1200 rpm for 10 to 20 minutes to obtain a primary blend. In the fourth step, a rheology modifier and the pre-composite flame retardant synergist are added to the primary blend, and the mixture is further mixed at 110 to 130 degrees Celsius at a speed of 800 to 1200 rpm for 15 to 25 minutes to obtain a secondary blend. In the fifth step, the secondary blend is cooled to below 60 degrees Celsius, discharged, and sieved to obtain the composite heat stabilizer.

9. The preparation process according to claim 8, characterized in that, In the first step, the surface modifier in the ethanol dilution solution has a mass concentration of 20% to 30%, and the spray addition rate is 5 to 10 ml per minute; the material temperature of the high-speed mixer is controlled by the jacket circulating water, and the temperature fluctuation does not exceed ±2 degrees Celsius; in the second step, the dispersant is stearic acid, and the addition amount is 0.5% to 1% of the total mass of ammonium molybdate and zinc borate; the ball mill uses zirconia balls as the grinding medium, and the ball-to-material mass ratio is 3:1 to 5:

1.

10. The preparation process according to claim 8, characterized in that, During the mixing process in the third and fourth steps, the lid of the high-speed mixer is closed, and the mixing chamber is filled with nitrogen for protection, with a nitrogen flow rate of 2 to 5 liters per minute; in the fifth step, sieving is done using a standard sieve of 80 to 120 mesh.